Influence of drying treatment on the physical and chemical properties of cucumber. - Henriques, Francisca (2011)
The present study evaluates the effect of drying treatments such as convective air drying and freeze-drying on the colour, texture, chemical properties (ash, sugars, fibre and vitamin C), phenolic compounds and antioxidant activity of cucumber. The trials in the convective chamber were done at 40 ºC and 60 ºC, in the drying tunnel were done at 60ºC and in the freeze dryer were done at -50ºC. It was possible to conclude that the air drying at 60 ºC (drying chamber and drying tunnel) produces small changes in colour of cucumber whereas air drying at 40 ºC and freeze drying originate more intense colour changes. With relation to texture it has been possible to deduce that the skin is harder than the peel in the fresh product, and that increasing drying temperature increases the hardness of the peel. In terms of ashes it was possible to verify that all values are similar but the value more similar to the fresh product was the one dried at 40ºC. The sugars contents (reducing, non reducing and total), were higher for the freeze drying and the trials for air drying at 60ºC (chamber and tunnel). Regarding fibres, it was found out that the higher value was obtained for air drying at 60ºC and the lower for freeze drying. In terms of vitamin C it has been possible to conclude that all treatments have a very pronounced effect in its reduction. In terms of antioxidant activity and phenolic compounds it is possible to verify that the different drying treatments are quite similar and do not produce significant reductions as compared to the fresh product.